MAKNA MAHAR DALAM ALQURAN (Kajian Historis-Antropologis) - Mochamad Tholib Khoiril Waro (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2019)
This study discusses the meaning of dowry contextually by using a historical-anthropological approach, assuming the dowry verse does not descend in empty space, but descends in the midst of the seventh-century ignorance Arab society which already has deep-rooted traditions. Anthropologically, the meaning of the dowry tradition is inseparable from the dynamics of culture that existed at that time. The scope of this study includes four things, first, the tradition of mahr in the ignorance period, second, the dialectic of God's revelation with the dowry tradition and the third review of Tasyakkul-Tasykil Nasr Hamid Abu Zayd's theory and the fourth, anthropological studies of religion as culture with Geertz's theory model of reality and model for reality. In this study, there is a dialectic between the revelation of God and the tradition of dowry in the ignorant Arab community who consider dowry as a medium of exchange for women to be married. Alquran is present, by adopting the tradition of dowry that has been running but constructs the meaning and practice of dowry based on the world view Alquran. Alquran means dowry as a mandatory gift for proof of love and sincerity (saduqat) which is given voluntarily (nihlah) with the intention of worshiping Allah.